Cost-Effectiveness of Short-Course Radiation Plus Temozolomide for the Treatment of Newly Diagnosed Glioblastoma Among Elderly Patients in China and the United States - Chen, Jigang; Tong, Xin; Han, Mingyang; Zhao, Songfeng; Ji, Linjin; Qin, Yongkai; He, Zilong; Pan, Yuesong; Wang, Chunhui; Liu, Aihua (Frontiers in Pharmacology, 2021)
Background: Glioblastoma multiforme (GBM) is a fatal type of brain tumor with a high incidence among elderly people. Temozolomide (TMZ) has proven to be an effective chemotherapeutic agent with significant survival benefits. This study aimed to evaluate the economic outcomes of radiotherapy (RT) and TMZ for the treatment of newly diagnosed GBM in elderly people in the United States (US) and China. Methods: A partitioned survival model was constructed for RT plus TMZ and RT alone among patients with methylated and unmethylated tumor status. Base case calculations and one-way and probabilistic sensitivity analyses were performed. Life-years, quality-adjusted life-years (QALYs), costs (in 2021 US dollars [$] and Chinese Yuan Renminbi [¥]), and incremental cost-effectiveness ratios (ICERs) were calculated. Results: RT plus TMZ was found to be associated with significantly higher costs and QALYs in all groups. Only US patients with methylated status receiving RT plus TMZ had an ICER ($89358.51) less than the willingness-to-pay (WTP) threshold of $100000 per QALY gained when compared with receiving RT alone. When the WTP threshold ranged from $100000 to $150000 from the US perspective, the probability of RT plus TMZ being cost-effective increased from 80.5 to 99.8%. The cost of TMZ must be lower than ¥120 per 20 mg for RT plus TMZ to be cost-effective among patients with methylated tumor status in China. Conclusion: RT plus TMZ was not cost-effective in China, and a reduction in the TMZ price was justified. However, it is highly likely to be cost-effective for patients with methylated tumor status in the US.